"Hot hand" in the National Basketball Association point spread betting market: A 34-year analysis - Benjamin Waggoner; Daniel Wines; Brian P. Soebbing; Chad S. Seifried; Jean Michael Martinez (International Journal of Financial Studies, 2014)
Several articles have looked at factors that affect the adjustments of point spreads, based on hot hands or streaks, for smaller durations of time. This study examines these effects for 34 regular seasons in the National Basketball Association (NBA). Estimating a Seemingly Unrelated Regression model using all 34 seasons, all streaks significantly impacted point spreads and difference in actual points. When estimating each season individually, differences emerged particularly examining winning and losing streaks of six games or more. The results indicate both the presence of momentum effects and the gambler's fallacy.
Keywords: 330; basketball; hot hand; streak; point spread; NBA (National Basketball Association) basketball; hot hand; streak; point spread; NBA (National Basketball Association)